A study on the multiple friction joint tension piles subjected to large horizontal displacements - Saidy, Mohammad Fahim. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Tension piles supporting some vital structures such as transmission towers, offshore wind turbines, jetties, chimneys, submerged floating tunnels, and tension leg platforms, are, often, subjected to large horizontal displacements. Experimental studies have been conducted on a type of pile, known as multiple friction joint piles developed at Boğaziçi University, to investigate the response and capacity of piles under combined large horizontal displacement and tensile forces, and to observe the effect of some parameters such as tensile forces, pile rigidity, and soil stiffness on the capacity and behavior of tension piles. The tests were conducted by placing multiple friction joint pile, or MFJP, having 34 cm length and five centimeters width, in a special large size large displacement direct shear apparatus and applying lateral or combined lateral and tensile loadings at the head of them. The head displacements of the piles and the lateral load on the piles were measured during the experiments to draw the load-displacement curves at the head of the piles. The model piles' inclination was also measured about the model piles longitudinal axis with the help of inertial measurement unit sensors. It was observed that as the pile's rigidity increases, the load-pile head displacement curve gets steeper and the pile head displacement at which the ultimate lateral load reaches decreases. The lateral capacity of the piles increases when the soil stiffness increases. The post-tension force on the wire, keeping the mortar blocks together in the multiple friction joint model pile, increases up to a displacement equal to the ultimate lateral displacement or the displacement at which soil failure occurs. The multiple friction joint piles subjected to large horizontal displacements have the capacity to undergo large deformations in the order of one pile's width without breakage. When the piles are subjected to both lateral displacement and tensile force, they experience a decrease in their lateral capacity compared to that of the piles subjected to lateral displacement alone.
Keywords: Deep-sea moorings.; Piling (Civil engineering)